The use of Crassostrea Virginica as lost circulation material in water-based drilling mud (2014)
Lost circulation of drilling fluid results in higher operational expenses which makes it imperative to design the fluid, such that minimal invasion of the fluid occurs in the formation. To achieve this, Lost Circulation Materials (LCM) are required which is expected to seal the fractures hence, the performance of Oyster Sea-shells (Crassostrea Virginica) as a lost circulation material is being investigated knowing that it is rich in Calcium Carbonate. Sea shells were prepared, pulverized and sieved to obtain fine grain particles which were analyzed in the laboratory for various properties. A fractured zone lost circulation test procedure was employed using a medium-sized fracture at 1000 psi. pressure drop and temperature of 8080F. The tests were performed in triplicates and the rheological and gel strength results were obtained. It was seen that although the Oyster Sea shell is not a viscosifier, it passes API acceptability test for API acceptable range of Plastic Viscosity and Yield Point. The plastic viscosity and Yield point of the mud were compared to that of the VG Gel and the trend observed was a good indication that the Oyster Sea shell would support Wyoming bentonite. Locally sourced Oyster Sea-shell can be used as a lost circulation material as its fine-sized grades performed excellently in controlling mud loss for the water-based mud in the laboratory. The 2:1 blend of Oyster Sea-shell outperformed the 2:1 blend of coarse and medium ground walnut shells in some of the water-based drilling mud tested; hence, the Oyster sea shell is a suitable substitute for conventional LCMs.